Marketing environment analysis as the key component of the company’s competitiveness evaluation - Bronskaia, Tatiana A. (Journal of the Belarusian State University. Economics, 2018)
The article analyses the marketing environment of Belgosstrakh. Сompetitiveness in a modern economy is the main factor of the commercial success of insurance enterprise. This, in turn, depends on the management quality and the competitiveness of the financial services and products offered. The author analyzed internal and external environment of the enterprise. Such factors as insurance product, prices, distribution channels, regional consumer penetration regarded as the enterprise index competitiveness. In the article used Porter’s Five Forces to conduct comparative analysis and expert evaluation method for PESTLE analysis.
Keywords: the marketing environment; Porter five forces industrial analysis; the competitiveness of an enterprise; insurance product; distribution channels